Betrayal the life and lies of Bernie Madoff - Kirtzman, Andrew (HarperCollins Publisher, 2009)
Discusses the multi-billion dollar Ponzi scheme masterminded by Bernard Madoff, including his motives for the financial betrayal and others who were involved in the scheme.